The Maiden of Orleans A Romantic Tragedy - Schiller, Friedrich, 1759-1805; Krumpelmann, John T., 1892-1986; Project Muse; Project Muse. (Project Muse, 2020)
First published as an American contribution to the 1959 bicentennial celebration of Friedrich Schiller's birth, Krumpelmann's translation of the poet's Joan of Arc drama retains the iambic pentameter of the original. This revised second edition, published in 1962 following critical acclaim, corrects typographical errors and includes some changes to the text.
Issued as part of book collections on Project MUSE.
Description based on print version record.
Keywords: Joan, -- of Arc, Saint, -- 1412-1431 -- Drama; Christian women saints -- Drama; France -- History -- Charles VII, 1422-1461 -- Drama; Electronic books; Tragedies (Drama); Electronic books